Effects of Schoenoplectus americanus (Pers.) Volkart Ex Schinz & R.Keller and Phragmites australis (Cav.) on the Water Quality Improvement of Moderately Saline Wastewater - Estrada-Loredo, Sarahi Josefina; Cisneros-Almazán, Rodolfo; Soto-Peña, Gerson Alonso; Hernández-Morales, Alejandro; del Socorro Santos-Díaz, María (Wetlands (Wilmington, N.C.), 2025)
Schoenoplectus americanus and Phragmites australis have a great potential for phytoremediation. In this study, the ability of these plants to improve the quality of moderately saline wastewater was tested. Both species were adapted to wastewater using two protocols. In the first, plants were directly exposed to undiluted or diluted wastewater at 12.5%, 25% and 50%. In the second protocol, the plants were gradually acclimated to 12.5%, and then to 25%, 50% diluted and undiluted wastewater for 20 days. Both processes were performed without using substrates. The efficiency of salt removal was assessed by employing plants adapted to undiluted wastewater over a period of 6 months. Direct exposure of S. americanus to wastewater resulted in a 50% reduction in stem height in undiluted wastewater and an arrest of root development in 25%, 50% and 100% wastewater. An exudation of salts was observed in the stem in undiluted wastewater. Shoot formation was not significantly affected. Progressive exposure to wastewater improved stem length by 23% and shoot formation by 13% in 12.5% diluted wastewater. Direct and progressive exposure of Phragmites australis to wastewater did not affect stem development, and increased the number of shoots (24–30%). Root growth reduction was observed during direct exposure to wastewater. Both species improved wastewater quality by reducing 0.8 units pH, as well as the concentration of nitrite (98%), nitrate (50-90%) and orthophosphate (50-90%) after 21 days. Therefore, S. americanus and P. australis are a viable option for treating moderately saline wastewater.